Detecting trends in 10-day rainfall amounts at five sites in the state ofSão Paulo, Brazil - Blain, Gabriel Constantino; Bardim-Camparotto, Ludmila (Acta Scientiarum. Technology, 2014)
The temporal distribution of the rainfall events within a crop growing season plays a crucial role on the crop yield. In this way, the main goal of this study was to evaluate the presence of climate trends in the 10-day rainfall totalsobtained from five weather stations in the State of São Paulo, Brazil (1951-2012).The autocorrelation function, the Run test and the Durbin-Watson test indicateda lack of significant serial correlation in theseseries. The wavelet analysis revealed no conclusive evidence of periodicities in the temporal variability of this variable. According to the Mann-Kendall test, most of the 10-day rainfall amounts obtained from the five weather stations shows no significant trends. However, for the locations of States Campinas, Pindorama and Ribeirão Preto, the significant decreasing trends observed during the 2nd and 3rd ten days of October suggests a possible change in the climatic patterns of these locations, which may be linked to a delay in the return of the rainy season. Â  Â 